2012
DOI: 10.1039/c2jm35556f
|View full text |Cite
|
Sign up to set email alerts
|

Organic dyes containing oligo-phenothiazine for dye-sensitized solar cells

Abstract: A series of organic dyes containing oligo-phenothiazine were synthesized and used effectively on the fabrication of dye-sensitized solar cells (DSSCs). In these compounds the phenothiazine moiety functions both as an electron donor and as a p-bridge. These materials exhibit considerably high values of open-circuit voltage (V oc ) ranging from 0.78-0.83 V under an AM1.5 solar condition (100 mW cm À2 ). Two kinds of substituents, i.e., hexyl and hexyloxyphenyl groups, were added onto the N(10) of phenothiazine f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(29 citation statements)
references
References 41 publications
0
29
0
Order By: Relevance
“…The reference dye C 6 PTZ was synthesized according to previous report [49]. The synthetic routes to the dyes WD14 and WD15 are shown in Scheme 2.…”
Section: Synthesismentioning
confidence: 99%
“…The reference dye C 6 PTZ was synthesized according to previous report [49]. The synthetic routes to the dyes WD14 and WD15 are shown in Scheme 2.…”
Section: Synthesismentioning
confidence: 99%
“…The dye sensitizer plays a crucial factor in the performance of DSSC, both on power conversion efficiency (η) as well as on device stability. Various kinds of organic dyes based on coumarin, 6 phenothiazine, [7][8][9][10] cyanine, 11 indoline, 12 triphenylamine, [13][14][15][16][17][18][19][20] derivatives have been shown to work effectively for DSSC. In contrast to metal complexes, organic dyes have been extensively explored in recent years due to their low cost, environmental friendliness, high molar absorption coefficient, tunable spectra, and others.…”
Section: Introductionmentioning
confidence: 99%
“…A high absorption coefficient in the visible wavelength will increase the value of shortcircuit current density (J sc ). 8,10 The structure of phenothiazine contains an electronrich heterocycle made with sulfur and nitrogen. However, rod-like molecules may magnify aggregate formation between molecules and facilitate the recombination of electrons with triiodide electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…Organic dyes containing oligo‐phenothiazine were used as both the electron donor and as the π‐conjugated spacer in sensitizers for DSC. It is additionally reported that long π‐bridges can adversely affect photovoltaic device performance . In this study we combine these concepts to systematically varied the π‐bridge length by introducing 0, 1, or 2 phenothiazine units between the donor and acceptor.…”
Section: Introductionmentioning
confidence: 99%